Method for bright zinc plating suppressing whisker formation and zinc cyanide plating bath composition therefor

KR103030718B1Active Publication Date: 2026-10-13SAEWON METAL
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
KR1020260100310
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-10-13
Estimated Expiration
2046-06-02

Smart Images

  • Figure 112026067081239-PAT00013_ABST
    Figure 112026067081239-PAT00013_ABST
Patent Text Reader

Abstract

The present invention relates to a bright zinc plating method for suppressing whisker generation and a zinc cyanide plating bath composition for the same. By mixing and adding 0.2 to 1.0 mL / L of saccharin and 0.5 to 2.0 mL / L of butanediol to a basic zinc cyanide plating bath comprising 70 to 80 g / L of sodium hydroxide, 50 to 75 g / L of sodium cyanide, 20 to 30 g / L of zinc, and a brightener, the invention effectively relaxes the compressive stress inside the plating layer to suppress whisker generation without changing the existing inline plating process or additional heat treatment, and simultaneously provides a bright zinc plating method and a zinc cyanide plating bath composition that achieve a glossiness of 75 GU or higher, a plating current efficiency of 75% or higher, no occurrence of red rust in a salt spray test for 240 hours, and excellent adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a zinc plating technology for rust prevention of electrical and electronic components, and more specifically, to a bright zinc plating method that effectively suppresses whisker formation by relieving internal stress in the plating layer by adding a mixture of saccharin and butanediol in a certain ratio to a zinc cyanide plating bath, and to a zinc cyanide plating bath composition for the same.

[0002] The present invention has a technical feature in that, unlike conventional whisker suppression methods that involve additional processes or additional equipment investment, such as zinc-nickel alloy plating or post-plating heat treatment processes, it achieves the same whisker suppression effect in-line of the existing zinc cyanide plating process by simply adding additives. Background Technology

[0003] Galvanizing is the most common and economical surface treatment method for rust prevention of steel materials, and it is applied in almost all industrial sectors, including automotive parts, electrical and electronic components, construction materials, telecommunications equipment, and structural materials, server racks, and supports for data centers. Galvanizing is based on the principle of preventing corrosion by precipitating zinc, which has a higher ionization tendency than iron, onto the surface of the material to act as a sacrificial anode.

[0004] Zinc plating methods are broadly classified into hot-dip galvanizing and electrogalvanizing, and electrogalvanizing is primarily used in the field of electrical and electronic components where precise thickness control and a uniform appearance are required. Electrogalvanizing is further classified into cyanide baths, alkaline non-cyanide baths, chloride baths, and sulfate baths depending on the type of plating bath used. Among these, although zinc cyanide plating entails the burden of wastewater treatment due to the use of sodium cyanide (NaCN), it is still widely used in the automotive and electrical and electronic component fields to this day because it provides the most stable results when plating parts with complex shapes, offering excellent uniformity, throwing power, gloss, and adhesion of the plating layer.

[0005] Meanwhile, the phenomenon in which fine single-crystal metal fibers spontaneously grow over time on a plated metal surface is called a whisker. Whiskers typically grow in the form of hair with a diameter of several micrometers and a length of several micrometers to several millimeters, causing electrical short circuits between adjacent conductors or delaminating and scattering, depositing in the form of fine particles on other parts to cause secondary failures.

[0006] Whiskers are originally the most well-known problem in tin (Sn) plating and have been treated as a critical reliability issue in the electronics industry since the widespread adoption of lead-free (Pb-free) soldering in accordance with RoHS regulations. However, whiskers have recently been reported in zinc plating as well, and numerous cases have been confirmed in environments where large amounts of zinc-plated steel are used, particularly in data centers, server rooms, and computer rooms, where whiskers detach and scatter, entering the server interior and causing system downtime due to electrical short circuits.

[0007] Although there are various theories regarding the causes of whisker formation, it is generally accepted that residual compressive stress within the plating layer is the primary driving force behind whisker growth. In other words, the mechanism involves compressive stress accumulated between grains during the plating process inducing the diffusion of metal atoms along the grain boundaries on the surface of the plating layer, leading to the spontaneous extrusion of single-crystal fibers from weak points on the surface due to this atomic diffusion. This stress accumulates through various factors, including (i) residual stress resulting from grain refinement immediately after plating, (ii) stress caused by differences in the coefficient of thermal expansion between the plating layer and the substrate due to changes in ambient temperature, (iii) the redistribution of hydrogen (H) remaining within the plating layer over time, and (iv) grain rearrangement over time.

[0008] In particular, in environments where operation takes place for a long time under constant temperature and humidity conditions, such as data centers, stress relaxation of the plating layer persists slightly. At this time, metal atoms at the grain boundaries are extruded to the surface as a stress release path, forming whiskers. Since the constant temperature and humidity conditions of data centers coincide with the critical conditions for whisker growth, it is reported that even with the same plating specifications, whiskers are not observed in general environments but are found in large quantities only in data center environments.

[0009] Methods for suppressing whiskers in zinc plating known until recently are broadly classified as follows. First, there is the method of employing zinc-nickel (Zn-Ni) alloy plating. This method aims to simultaneously refine grain size and relieve stress by co-depositing nickel into zinc grains at a certain ratio (typically 5 to 15 wt%); however, it has the disadvantage of increasing costs due to the high unit cost of the plating bath and the requirement of a separate treatment system for wastewater treatment. Second, there is a method of artificially relaxing internal stress in the plating layer by performing a separate heat treatment (typically at 150 to 200°C for 1 to 24 hours) after zinc plating. While this is a relatively simple method, it has limitations in that it requires additional separate heat treatment equipment and energy costs, and does not align with carbon neutrality policies and ESG management principles. Third, there is a method of improving stress compatibility between the base material and the plating layer by performing copper (Cu) strike plating before zinc plating; however, since this also requires the addition of a separate plating tank, significant modifications to existing inline equipment are unavoidable.

[0010] As described above, since all conventional whisker suppression methods involve (i) changing the plating bath, (ii) adding an additional heat treatment process, or (iii) adding an additional plating layer, no method has yet been reported to suppress whiskers using only simple additives while maintaining the existing zinc cyanide plating inline. Therefore, there is an urgent need to develop a method that can effectively suppress whisker generation by introducing an additive with a stress-relieving function into the plating bath without essentially changing the composition and operating conditions of the existing zinc cyanide plating bath.

[0011] Meanwhile, data centers and server facilities operate 24 hours a day, year-round due to their nature, and given that a short circuit caused by whiskers results in massive service interruption costs, ensuring the reliability of plating materials to prevent whisker formation has become an inevitable requirement. In particular, with the expansion of next-generation IT infrastructure such as global cloud services, artificial intelligence (AI) learning infrastructure, Internet of Things (IoT) processing facilities, and 5G communication infrastructure, the scale and number of data centers are increasing explosively, and the potential risk caused by whisker problems is also increasing proportionally.

[0012] In addition, whisker suppression plating technology is expected to become increasingly important across future industries, as whiskers can reduce the operational reliability of precision components or biosignal measurement electrodes in the medical device sector, cause short-circuit accidents in high-density circuits such as ECUs, BCMs, and infotainment modules in the automotive electronics sector, and cause insulation breakdown in DC high-voltage circuits in the ESS and solar inverter sectors.

[0013] To meet these industrial demands, a new plating technology is required that not only suppresses whiskers but also simultaneously satisfies five requirements: (a) not affecting the productivity of existing plating lines, (b) not requiring additional equipment investment, (c) not incurring additional energy consumption, (d) not significantly increasing the burden of wastewater treatment, and (e) maintaining conventional plating quality factors, such as gloss, current efficiency, corrosion resistance, and adhesion of the plating layer, at an equivalent or higher level.

[0014] In order to satisfy these industrial requirements, the inventors developed a whisker-suppressing bright zinc plating method that satisfies all five of the above requirements by mixing and adding saccharin, which is strongly adsorbed on the cathode surface of a zinc cyanide plating bath and inhibits crystal growth, and butanediol, which performs a smoothing and leveling function at the cathode interface and simultaneously relaxes the compressive stress of the grain boundaries, in a certain ratio. Prior art literature

[0015] Korean Published Patent Application No. 10-2020-0079049, Korean Registered Patent Application No. 10-1345678, Japanese Registered Patent Application No. 2892601. Patent Document 1 (Korean Published Patent Application No. 10-2020-0079049) discloses a method for gradually reducing internal stress by forming a plating layer into a two-layer structure consisting of a primary plating layer and a secondary plating layer. However, this method has the disadvantage that equipment investment increases significantly and operational burdens, such as anode management and bath concentration management, increase twofold, as at least two plating tanks must be installed in-line. In addition, if the crystal structure of the secondary plating layer and the crystal structure of the primary plating layer are not sufficiently consistent, there is a risk that additional interfacial stress may occur, thereby increasing the number of whisker nucleation sites. Patent Document 2 (Korean Registered Patent Publication No. 10-1345678) discloses a method for preventing whisker formation by heat treating under specific temperature (typically 150 to 200°C) and time (typically 1 to 24 hours) conditions after zinc plating. However, this method has the disadvantages of (i) requiring additional separate heat treatment furnaces and conveyor equipment, (ii) requiring massive energy to heat and cool parts, which does not comply with carbon neutrality policies, and (iii) reducing glossiness and deteriorating appearance quality due to crystal changes in the plating layer during heat treatment. Patent Document 3 (Japanese Registered Patent Publication No. 2892601) discloses a method of performing copper (Cu) strike plating before zinc plating, followed by zinc cyanide plating. This is an approach that introduces an intermediate layer with excellent stress compatibility between the base material and the zinc plating layer, but it has the disadvantages of (i) requiring additional management of a separate copper strike plating tank and anode and bath composition for it, (ii) the burden of washing is high in in-line connection with an alkaline zinc cyanide plating bath because the copper plating bath is typically acidic, and (iii) line management becomes more difficult because if copper is leached in small amounts into the alkaline cyanide bath, it causes cumulative contamination in the plating bath.As described above, all conventional whisker suppression methods involve additional facility investment or additional energy consumption, such as (a) additional plating baths, (b) additional heat treatment furnaces, or (c) alloy anodes or new plating baths. In contrast, the present invention achieves an equivalent whisker suppression effect simply by adding a mixture of saccharin and butanediol in a certain ratio to an existing zinc cyanide plating bath, thereby possessing an essential differentiation that overcomes all the limitations of the prior art at once. The problem to be solved

[0016] The present invention was devised to solve the problems of the aforementioned prior art, and the objective of the present invention is to provide a bright zinc plating method that can suppress whisker formation by effectively relieving internal stress in the plating layer by adding a mixture of saccharin and butanediol in a certain concentration range to the plating bath without substantially changing the basic composition and inline working conditions of the existing zinc cyanide plating bath.

[0017] Another objective of the present invention is to provide a zinc cyanide plating bath composition used in the bright zinc plating method, comprising 0.2 to 1.0 mL / L of saccharin and 0.5 to 2.0 mL / L of butanediol, which simultaneously achieves grain refinement of the plating layer and stress relief compared to the case where only a conventional primary brightener is used alone.

[0018] Another objective of the present invention is to provide a zinc-plated material plated by the above-described gloss zinc plating method, which has excellent adhesion with no whiskers substantially occurring even after being left for 5 days under constant temperature and humidity conditions of 80°C, a glossiness of 75 GU or higher, a plating current efficiency of 75% or higher (average of low-current and high-current sections), no red or blue rust occurring in a salt spray test for 240 hours, and no peeling of the plating layer.

[0019] Another objective of the present invention is to provide an eco-friendly whisker suppression plating method that is compatible with carbon emission reduction and ESG management, as it does not rely on conventional zinc-nickel alloy plating or post-plating heat treatment, thereby not entailing additional facility investment or additional energy consumption. means of solving the problem

[0020] To achieve the above objective, one aspect of the present invention provides a bright zinc plating method comprising the step of immersing a workpiece in a zinc cyanide plating bath and applying current to form a zinc plating layer on the surface of the workpiece, wherein the zinc cyanide plating bath is composed of 0.2 to 1.0 mL / L of saccharin and 0.5 to 2.0 mL / L of butanediol added to a base bath comprising 70 to 80 g / L of sodium hydroxide (NaOH), 50 to 75 g / L of sodium cyanide (NaCN), 20 to 30 g / L of zinc (Zn), and a brightener.

[0021] The above zinc cyanide plating bath preferably has a zinc concentration ratio relative to sodium cyanide (NaCN / Zn, commonly referred to as the M ratio) of 2.0 to 3.0, and more preferably about 2.5.

[0022] The above saccharin has sulfonimide groups within its molecule that are advantageous for cathodic adsorption, and when plating, it is adsorbed onto the cathodic surface and inhibits the crystal growth rate, thereby refining the crystal grains of the plating layer, while simultaneously acting to primarily relax the internal stress of the plating layer by being co-precipitated in small amounts within the plating layer.

[0023] The above butanediol is preferably one or more selected from the group consisting of 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, and combinations thereof, and more preferably includes 2-butyne-1,4-diol. Due to the two hydroxyl groups (-OH) and chain structure within the molecule, butanediol exhibits excellent smoothing and leveling action at the cathode interface, and in combination with grain refinement by saccharin, it dramatically improves the flatness of the plating layer surface and additionally relaxes residual compressive stress at the grain boundaries.

[0024] The zinc cyanide plating bath of the present invention dramatically improves the whisker generation suppression rate compared to the case where only one of the components is used alone, as it is a combined effect of both components rather than a simple sum of saccharin and butanediol. As confirmed in the examples described below, when saccharin or butanediol is used alone, whiskers remain and are generated, but when 0.2 to 1.0 mL / L of saccharin and 0.5 to 2.0 mL / L of butanediol are added simultaneously, whiskers are not substantially observed even under conditions of constant temperature and humidity at 80°C for 5 days.

[0025] A bright zinc plating method according to one embodiment of the present invention includes the step of immersing a workpiece in a zinc cyanide plating bath and applying current under conditions of a current density of 2 to 8 A / dm² and a bath temperature of 20 to 30℃ to form a zinc plating layer with a thickness of 3 to 15 μm on the surface of the workpiece.

[0026] A bright zinc plating method according to another embodiment of the present invention further comprises, after the zinc plating layer forming step, (i) a washing step, (ii) a nitric acid activation step, (iii) a colored chromate or trivalent chromium passivation step, and (iv) a washing and drying step.

[0027] Another aspect of the present invention provides a zinc cyanide plating bath composition for whisker inhibition comprising 70 to 80 g / L sodium hydroxide, 50 to 75 g / L sodium cyanide, 20 to 30 g / L zinc, 0.2 to 1.0 mL / L brightener and saccharin, and 0.5 to 2.0 mL / L butanediol.

[0028] Another aspect of the present invention provides a galvanized material comprising a galvanized layer formed by the above-described polished galvanizing method, characterized in that whiskers do not form even after being left for 5 days under constant temperature and humidity conditions of 80°C. Effects of the invention

[0029] According to the present invention, a glossy zinc plating layer in which whiskers are substantially not generated can be obtained by simply adding a mixture of saccharin and butanediol in a certain ratio to the plating bath while maintaining the inline of the existing zinc cyanide plating process as is, under conditions of constant temperature and humidity of 80°C for 5 days.

[0030] Furthermore, according to the present invention, since a whisker suppression effect can be achieved without the installation of an additional plating bath, substitution with an alloy plating bath, or a separate heat treatment process, it does not entail facility investment costs or additional energy consumption, and aligns with carbon emission reduction and ESG management principles.

[0031] In addition, according to the present invention, due to the synergy of grain refinement by saccharin and stress relief and smoothing by butanediol, the glossiness of the plating layer is improved to 75 GU or higher, and the average plating current efficiency of the low-current and high-current sections is improved to 75% or higher, thereby simultaneously improving appearance and productivity compared to the case where only a conventional primary brightener is used alone.

[0032] In addition, according to the present invention, since the crystal grains of the plating layer are refined and the surface smoothness is improved, the adsorption and uniformity of the subsequent chromate or trivalent chromium passivation treatment are improved, and excellent corrosion resistance is exhibited in which no red rust occurs for 240 hours in a salt spray test according to KS D 9502.

[0033] In addition, according to the present invention, when applied to electrical and electronic components requiring reliability, such as structural materials for data centers and server rooms, medical device frames, automobile wiper linkages, and server racks for ESS devices, short-circuit accidents caused by whiskers and secondary failures caused by fine particle scattering can be fundamentally prevented.

[0034] In addition, according to the present invention, the residual stress of the plating layer is maintained at a low value of 60 MPa or less in measurements by the X-ray diffraction sin²Ψ method, and a stress reduction of about 50% or more is achieved compared to the residual stress of a conventional additive-free zinc cyanide plated material. This fundamentally blocks the accumulation of stress driving force over time, thereby ensuring long-term reliability in which whiskers do not form even after long-term exposure of 6 months or more.

[0035] In addition, according to the present invention, a uniform glossy appearance is obtained over a wide current density range of about 0.5 to 7.0 A / dm² in a Hull Cell test, so even when plating parts with complex shapes, a uniform plating layer can be formed over the entire shape without missing plating in low-current areas or rough appearance in high-current areas. Brief explanation of the drawing

[0036] Figure 1 is a schematic diagram illustrating the mechanism by which whiskers grow over time on a galvanized surface and cause an electrical short circuit with an adjacent conductor. FIG. 2 is an inline process flow diagram for zinc cyanide plating according to one embodiment of the present invention, illustrating the entire process from pretreatment steps such as degreasing, pickling, and rinsing to zinc plating, chromate treatment, and drying. FIG. 3 is a schematic diagram illustrating the mechanism of crystal growth inhibition and grain refinement by cathodic adsorption of saccharin according to one embodiment of the present invention. FIG. 4 is a schematic diagram illustrating the smoothing action and grain boundary stress relaxation mechanism by the adsorption of butanediol at the cathodic interface according to one embodiment of the present invention. FIG. 5 is a diagram comparing the cross-sectional crystal structures of a plating layer in each case of saccharin alone, butanediol alone, and saccharin-butanediol mixed addition according to one embodiment of the present invention. FIG. 6 is a diagram illustrating the whisker generation pattern on the surface of a specimen after a whisker acceleration test (80°C constant temperature and humidity for 5 days) according to one embodiment of the present invention, with respect to a comparative example and an example. FIG. 7 is a drawing illustrating the results of an external appearance evaluation of a Hull Cell test plate according to one embodiment of the present invention, compared with a comparative example and an embodiment. FIG. 8 is a graph showing the plating current efficiency according to one embodiment of the present invention, compared with the comparative example and the embodiment, for the low current section and the high current section, respectively. FIG. 9 is a graph showing the results of a salt spray test according to KS D 9502 of a plating layer according to one embodiment of the present invention, compared with a comparative example and an example over time. FIG. 10 is a drawing showing the results of an adhesion evaluation (bending test and tape peeling test) according to KS B 0804 of a plating layer according to one embodiment of the present invention, compared with a comparative example and an example. FIG. 11 is a scanning electron microscope (SEM) surface observation result of a plating layer according to one embodiment of the present invention, and is a figure comparing the grain size and surface morphology of the plating layers of Comparative Example 1 (no additive added) and Example 2 (saccharin 0.5 mL / L + butanediol 1.0 mL / L) at a magnification of 5,000. FIG. 12 is a graph showing the X-ray diffraction (XRD) analysis results of a plating layer according to one embodiment of the present invention, comparing the crystal orientation and residual stress measurement results for the plating layers of Comparative Example 1 and Example 2. FIG. 13 is a graph showing the X-ray photoelectron spectroscopy (XPS) analysis results of a plating layer according to one embodiment of the present invention, illustrating the trace co-precipitation pattern of saccharin and butanediol-derived components in the plating layer. FIG. 14 is a contour-type working window diagram illustrating the frequency of whisker generation in a plating layer according to changes in the concentration of saccharin and butanediol according to one embodiment of the present invention. FIG. 15 is a plating bath maintenance graph illustrating the change in additive concentration and the timing of replenishment according to the accumulation of plating amount of a zinc cyanide plating bath according to one embodiment of the present invention. Specific details for implementing the invention

[0037] The present invention will be described in more detail below. However, the following description relates to one embodiment of the present invention, and the technical scope of the present invention is not limited thereto.

[0038] 1. Basic composition of zinc cyanide plating baths

[0039] The zinc cyanide plating bath according to the present invention comprises (a) an alkali component, (b) a cyanide component, (c) a zinc component, (d) a brightener, and (e) saccharin and butanediol, which are key additives of the present invention. Each component will be described in detail below.

[0040] In zinc cyanide plating baths, zinc ions combine with cyanide ions to form anionic cyanide complexes ([Zn(CN)₄]² As an alkaline plating bath that forms ), the following four equilibrium reactions proceed simultaneously even with the same composition to determine the plating behavior.

[0041]

[0042] In the present invention, the concentrations of alkali, cyanide, and zinc components are limited to the range described below so that the equilibrium of (1) to (4) above is stably maintained. In particular, to suppress the hydrogen generation side reaction at the cathode, the additives described below (saccharin, butanediol) adsorb to the cathode interface and perform the role of improving the hydrogen generation overpotential.

[0044] 1.1 Alkaline component (sodium hydroxide)

[0045] In the present invention, sodium hydroxide (NaOH, caustic soda) is used as the alkali component. Sodium hydroxide maintains the pH of the plating bath in the alkaline range while simultaneously providing stability to the cyanide complex. The content of sodium hydroxide in the plating bath is preferably 70 to 80 g / L. If it is less than 70 g / L, the conductivity of the bath is insufficient, causing scattering and potentially reducing the hiding power; if it exceeds 80 g / L, the solubility of zinc increases excessively, potentially reducing the anode efficiency.

[0047] 1.2 Cyanide component (sodium cyanide)

[0048] In the present invention, sodium cyanide (NaCN, sodium cyanide) is used as the cyanide component. Sodium cyanide combines with zinc ions in the plating bath to form anionic cyanide complexes of the [Zn(CN)]²⁻¹ type, and these complexes become a key factor in determining the uniformity and hiding power of the plating bath. The content of sodium cyanide is preferably 50 to 75 g / L. If the content is less than 50 g / L, complex formation is insufficient, which lowers the uniformity of the plating layer, and if the content exceeds 75 g / L, not only does the burden of wastewater treatment increase, but there is also a risk that the plating efficiency may actually decrease.

[0050] 1.3 Zinc component

[0051] In the present invention, the zinc component is Zn² in the plating bath. or [Zn(CN)₄]² It exists in the form of a zinc equivalent content of 20 to 30 g / L. If the zinc content is less than 20 g / L, the plating speed decreases, leading to reduced productivity, and if it exceeds 30 g / L, the grain size becomes coarse, raising concerns about reduced gloss.

[0053] 1.4 Zinc-to-sodium cyanide ratio (M ratio)

[0054] In the present invention, the ratio of sodium cyanide concentration to zinc concentration, i.e., the M ratio (NaCN / Zn), is a key operational variable that determines the workability of the plating bath. If the M ratio is excessively low, the stability of the cyanide complex is insufficient, causing a white precipitate to form near the anode; if it is excessively high, the hiding power is improved, but the plating efficiency decreases rapidly. In the present invention, the M ratio is preferably 2.0 to 3.0, and more preferably about 2.5.

[0056] 1.5 Polish

[0057] In the present invention, the brightener is a component that imparts a glossy appearance to the plating layer, and the brightener conventionally used in zinc cyanide plating baths can be used as is. The core additive (saccharin, butanediol) described below in the present invention does not impair glossiness even when used in combination with such conventional brighteners, but rather complementarily improves glossiness.

[0059] 2. Key additive of the present invention

[0060] 2.0 Whisker Generation Mechanism and Inhibition Principle of the Present Invention

[0061] In order to clearly understand the mechanism of action of the additive of the present invention in suppressing whiskers, it is first necessary to examine the whisker generation mechanism in zinc plating by dividing it into the following four steps.

[0062] (1) Stage 1 - Stress accumulation phase: During the electroplating process, compressive stress accumulates at the grain boundaries as grains nucleate in a disordered manner. As the grains become coarser, the length of the grain boundaries themselves becomes shorter, but stress is concentrated at specific grain boundaries, forming stress concentration sites.

[0063] (2) Stage 2 - Stress-induced diffusion stage: As time progresses, zinc atoms at the grain boundaries begin to diffuse due to the stress gradient. At this stage, whiskers are not yet observed on the surface, but atomic rearrangement proceeds gradually near the grain boundaries.

[0064] (3) Third stage - Extrusion initiation: Zinc atoms are extruded from the stress concentration area toward the surface, forming initial whisker nuclei. At this stage, fine protrusions are observed on the surface, and the whisker length, which is usually identifiable with an optical microscope, is about 1 to 10 μm.

[0065] (4) 4th stage - Growth stage: Zinc atoms at the grain boundaries are continuously supplied through the initial nucleus, and whiskers grow into single-crystal fibers. Whiskers at this stage can grow to lengths ranging from tens of micrometers to several millimeters and cause short circuits with adjacent conductors.

[0066] In light of the mechanism described above, whisker suppression requires the simultaneous implementation of three approaches: (a) dispersing the occurrence of stress concentrations by refining the grain size, (b) alleviating stress gradients by relaxing compressive stresses at grain boundaries, and (c) blocking the path for stress concentrations to be extruded to the surface through surface smoothing.

[0067] The additive combination of the present invention corresponds precisely to the three approaches above. That is, saccharin is responsible for (a) grain refinement and (b) primary stress relaxation, and butanediol is responsible for (c) surface smoothing and (b) secondary stress relaxation. The combined use of the two components exhibits a synergy that simultaneously improves the three factors above, thereby dramatically improving the whisker suppression effect compared to when used alone.

[0069] 2.1 Saccharin

[0070] Saccharin (1,2-benzisothiazole-3(2H)-one 1,1-dioxide) is an organic compound of the aromatic sulfonimide series and is commonly known in the plating field as a primary brightener for nickel and zinc plating baths. Saccharin has sulfonimide groups (-SO₂-NH-) and carbonyl groups (C=O) within its molecule that can be strongly adsorbed onto the cathode surface, and thus exhibits the effect of inhibiting crystal growth when adsorbed onto the cathode.

[0071] In the present invention, saccharin acts to (i) refine the grains by adsorbing to the cathode surface and inducing an increase in crystal nucleation sites and a decrease in the crystal growth rate, (ii) offset a portion of the compressive stress by acting in the direction of tensile stress of the plating layer through trace co-precipitation within the plating layer, and (iii) reduce the whisker nucleation sites themselves through the refined grain boundaries.

[0072] In the present invention, the amount of saccharin added is 0.2 to 1.0 mL / L (based on a commercially available aqueous saccharin solution or a commercially available saccharin-containing brightener concentrate). If the amount is less than 0.2 mL / L, the grain refinement effect is insufficient, resulting in a negligible whisker suppression effect, and if the amount exceeds 1.0 mL / L, the ductility of the plating layer is excessively reduced, which may cause delamination or cracking during a bending test. More preferably, it is 0.3 to 0.8 mL / L, and even more preferably, about 0.5 mL / L.

[0073] The grain refinement effect of cathodic adsorption of saccharin is observed to result in the average grain size being reduced to 30 to 50% of that of a conventional bath. According to X-ray diffraction (XRD) analysis, the diffraction peaks of the (002) and (101) planes of the specimen plated in the saccharin-added bath of the present invention are broadened compared to a conventional bath, and from this, it can be confirmed that the grain size calculated by the Scherrer equation is reduced from an average of about 200 nm to about 80 to 100 nm.

[0074] In addition, the co-deposition of trace sulfur (S) in the plating layer by saccharin is confirmed by X-ray photoelectron spectroscopy (XPS) analysis, and the sulfur content in the plating layer is typically at the level of 100 to 500 ppm. This trace sulfur is dispersed between the grains, strengthening the strength of the grain boundaries while simultaneously partially offsetting the compressive stress in the plating layer in the direction of tensile stress.

[0076] 2,2 Butanediol

[0077] Butanediol is a general term for diol compounds having two hydroxyl groups (-OH) at both ends or in the middle of a four-carbon chain within a molecule. In the present invention, it refers to one or more selected from the group consisting of 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, and 2-butyne-1,4-diol (2-butyne-1,4-diol, which is a type of alkynyl diol and is typically classified together in the category of butanediol). Most preferably, it includes 2-butyne-1,4-diol.

[0078] Butanediol is adsorbed to the cathode interface and performs (i) smoothing and leveling functions to smooth out fine irregularities on the plated surface, (ii) changes the preferred orientation of crystal growth through the interaction between hydroxyl groups and the zinc surface to form isotropic grains, and (iii) further relaxes compressive stress near grain boundaries. In particular, alkynyl diols having a triple bond within the molecule, such as 2-butyne-1,4-diol, are adsorbed more strongly to the cathode surface to maximize synergy with saccharin.

[0079] In the present invention, the amount of butanediol added is 0.5 to 2.0 mL / L. If it is less than 0.5 mL / L, the smoothing effect is insufficient and the surface roughness is not sufficiently lowered, and if it exceeds 2.0 mL / L, the butanediol itself lowers the plating efficiency, which may result in incomplete plating of the low-current portion. More preferably, it is 0.8 to 1.5 mL / L, and even more preferably, about 1.0 mL / L.

[0080] The smoothing effect of butanediol is quantitatively confirmed by measuring surface roughness (Ra). While the surface roughness of a specimen plated in a conventional bath (Comparative Example 1) is an average Ra of 0.35 to 0.45 μm, the surface roughness of a specimen plated in the saccharin-butanediol mixed additive bath of the present invention is an average Ra of 0.15 to 0.20 μm, which is reduced to about 50 to 60% of the level of the conventional bath.

[0081] In addition, the grain boundary stress relaxation effect of butanediol is quantitatively confirmed by measuring the residual stress of the plating layer (XRD sin²Ψ method). While the residual compressive stress of specimens plated in a conventional bath is about 100 to 150 MPa, the residual compressive stress of specimens plated in the bath of the present invention is about 30 to 50 MPa, which is reduced to about 60 to 70% of the level of the conventional bath. This significant reduction in residual stress serves as the quantitative basis for the suppression of whisker formation.

[0083] 2.3 Synergistic Effects of Mixed Use of Saccharin and Butanediol

[0084] The core of this invention lies in the fact that the whisker formation rate is dramatically reduced when saccharin and butanediol are used in a mixture of both components in a certain ratio, compared to when each is used alone. This is because (i) the number of grain boundaries per unit area increases due to grain refinement by saccharin, and (ii) the stress concentration sites corresponding to whisker nucleation sites are effectively eliminated as smoothing and grain boundary stress relaxation by butanediol act additionally.

[0085] In particular, as a result of the inventors performing whisker acceleration tests (80°C constant temperature and humidity for 5 days) on various additive combinations, it was confirmed that the frequency of whisker occurrence was most effectively reduced under the condition of simultaneous addition of 0.2 to 1.0 mL / L saccharin and 0.5 to 2.0 mL / L butanediol, and this effect is evaluated as a synergistic effect that significantly exceeds the simple sum of each component.

[0087] 3. Plating Process

[0088] 3.1 Preprocessing

[0089] The bright zinc plating method of the present invention performs a conventional pretreatment process before plating. The pretreatment may be performed in the following order, for example: (i) alkaline degreasing, (ii) first rinse, (iii) pickling (typically 5 to 15% HCl), (iv) second rinse, (v) activation (about 1 to 5% NaCN or 1 to 5% HCl), and (vi) third rinse. The pretreatment is a step to ensure the adhesion of the plating layer by removing grease, contaminants, and oxides from the surface of the material to be plated, and the specific conditions thereof may be appropriately changed within a range that does not affect the effects of the present invention.

[0090] For the alkaline degreasing step, immersion degreasing is performed for 5 to 10 minutes at a temperature of 55 to 65°C using a degreasing solution containing, for example, 20 to 40 g / L sodium hydroxide, 15 to 30 g / L sodium carbonate, 5 to 15 g / L trisodium phosphate, and 1 to 3 mL / L surfactant. Depending on the degree of surface contamination, 1 to 3 A / dm² cathodic electrolytic degreasing may be used in combination.

[0091] For the pickling step, immersion pickling is performed for 3 to 5 minutes at room temperature using a pickling solution in which 1 to 3 g / L of a corrosion inhibitor (e.g., hexamethylenetetramine) is added to an 8 to 12% aqueous hydrochloric acid solution, for example. The pickling time is adjusted according to the thickness of the surface oxide film.

[0092] The activation step is a step for removing trace amounts of oxide or alkali residue remaining on the surface, and in the present invention, it is preferable to adopt a method of immersing in an aqueous sodium cyanide solution with a concentration of about 2 to 3 g / L at room temperature for 30 to 60 seconds. This improves compatibility with the subsequent zinc cyanide plating bath and contributes to securing the initial adhesion of the plating layer.

[0094] 3.2 Plating

[0095] The pretreated workpiece is immersed in the zinc cyanide plating bath of the present invention and current is applied to form a zinc plating layer on the surface. The plating conditions are as follows.

[0096] 1) Bath temperature: 20 to 30℃, preferably 23 to 27℃

[0097] 2) Current density: 2 to 8 A / dm², preferably 3 to 5 A / dm², more preferably about 4 A / dm²

[0098] 3) Plating time: Determined by the target thickness; typically, it takes about 5 to 20 minutes when aiming for a thickness of 5 µm.

[0099] 4) Plating thickness: 3 to 15 µm, preferably about 5 µm

[0100] 5) Anode: Zinc anode with a purity of 99.9% or higher, or a combination of a zinc anode and an insoluble anode

[0101] 6) Stirring: Air stirring or mechanical stirring, recommended stirring speed is a liquid flow rate of approximately 1 to 3 m / s.

[0103] 3.3 Post-processing

[0104] After the plating is completed, the plated material undergoes a first rinse with water, followed by activation with approximately 0.5 to 1.0% nitric acid (5 to 30 seconds), and then subsequent chromate or trivalent chromium passivation treatment. In the present invention, it is preferable to perform colored chromate treatment to meet the standard conditions of the whisker accelerated test; however, if compliance with environmental regulations is required, it may be replaced with trivalent chromium passivation treatment (e.g., black, colorless, or blue passivation). After post-treatment, water rinsing and hot air drying at 80°C or lower are performed.

[0106] 3.4 Inline Process Suitability

[0107] Since the additive of the present invention is a liquid chemical that is simply added to an existing zinc cyanide plating bath, it can be used by directly introducing it into the plating tank of an existing inline plating facility. No additional investment in equipment such as a separate plating tank, heat treatment furnace, or alloy anode is required.

[0109] 3.5 Analysis and Management of Plating Baths

[0110] Since the concentration of the plating bath components of the zinc cyanide plating bath of the present invention gradually fluctuates during operation, it is desirable to perform regular analysis and replenishment as follows to maintain constant plating quality.

[0111] (1) Analysis of zinc concentration: For example, it is analyzed by the EDTA titration method (ethylenediaminetetraacetic acid titration). Typically, analysis is recommended once a day, and the concentration is restored by adding zinc oxide (ZnO) or zinc cyanide (Zn(CN)₂) before the concentration reaches the lower limit (20 g / L) of the present invention.

[0112] (2) Sodium cyanide concentration analysis: For example, it is analyzed by silver nitrate (AgNO₃) titration. It is recommended to analyze once a day and replenish sodium cyanide before the concentration reaches the lower limit (50 g / L). Since sodium cyanide is gradually consumed by carbonation decomposition during plating, its concentration usually decreases slightly faster than that of zinc.

[0113] (3) Sodium hydroxide concentration analysis: For example, analysis is performed by hydrochloric acid titration (methyl orange indicator). Analysis is recommended 2 to 1 / 2 times a week, and sodium hydroxide is replenished before the concentration reaches the lower limit (70 g / L).

[0114] (4) Carbonate concentration management: Sodium carbonate accumulates in the plating bath due to the decomposition of sodium cyanide or the absorption of carbon dioxide from the atmosphere. If the concentration exceeds about 60 g / L, the viscosity of the plating bath increases, which lowers the plating uniformity. In this case, it is desirable to remove the carbonate by (a) replenishing fresh water after partial bleeding of the plating bath, or (b) freezing and separating the plating bath (usually, sodium carbonate precipitates as crystals when cooled to -5 to 0 ℃).

[0115] (5) Management of additive concentration: Although it is relatively difficult to directly quantitatively analyze saccharin and butanediol, which are the core additives of the present invention, they can be indirectly monitored by observing the appearance of the Hull Cell test plate (especially the gloss of the low-current section and the smoothness of the middle section) every day. Typically, it is recommended to add about 30 to 50 mL of saccharin and about 60 to 100 mL of butanediol per 1,000 Ah of plating.

[0116] (6) Management of Impurities: The main impurities that can accumulate in the plating bath are (a) iron (Fe), (b) lead (Pb), (c) cadmium (Cd), (d) copper (Cu), and (e) chromium (Cr). Among these, iron can accumulate in the plating bath at a level of about 20 to 50 mg / L without issue, but if it exceeds this amount, it causes fine defects in the plating layer, so regular decontamination (removal of precipitates by weak alkali treatment) or partial disposal and replenishment of fresh solution is required. Lead, cadmium, and chromium degrade gloss and whisker characteristics even at levels of 5 mg / L or higher, so care must be taken in line management to ensure they do not enter the plating bath.

[0118] 3.6 Bipolar Management

[0119] In the zinc cyanide plating of the present invention, it is preferable to use a zinc anode with a purity of 99.9% or higher. If the anode is left in a non-current state for a long time while immersed in the plating bath, an oxide film may form on the surface of the anode, which may reduce the anode efficiency. Therefore, when not in operation, it is preferable to remove the anode from the plating bath for storage or to apply a small current of about 0.1 to 0.5 A / dm² to the anode to prevent the formation of an oxide film.

[0120] It is preferable to immerse the anode in an anode bag (typically made of polypropylene or cotton cloth) and place it in the plating bath. The anode bag prevents fine powder or sludge that may be generated from the anode from entering the plating bath and causing floating defects. The anode bag is typically replaced every 6 months to 1 year.

[0122] 3.7 Work Environment and Safety

[0123] Since the zinc cyanide plating bath of the present invention contains sodium cyanide, safety management of the working environment is important. The plating bath must be maintained in an alkaline state (pH 12 or higher), and since contact with acidic liquids can generate toxic hydrogen cyanide (HCN) gas, a sufficient rinsing process must be placed between the pickling bath and the plating bath.

[0124] A local exhaust system (push-pull or lateral exhaust) must be installed at the top of the plating bath to exhaust fine mist and gases generated from the surface of the plating bath to the outside, thereby minimizing respiratory exposure of workers. Workers must wear alkali-resistant and eye-resistant protective gloves, safety glasses, a waterproof apron, and respiratory protection.

[0125] The wastewater from the plating bath must be discharged in compliance with environmental laws after undergoing cyanide oxidation treatment (typically alkaline chlorination with sodium hypochlorite) and heavy metal precipitation treatment. Both saccharin and butanediol, which are the core additives of the present invention, are used in trace amounts and are biodegradable, so they do not cause an additional burden on the wastewater treatment process.

[0127] 4. Examples

[0128] The present invention will be explained in more detail below through examples and comparative examples. However, the following examples are intended to illustrate the present invention and do not limit the scope of the present invention.

[0130] 4.1 Preparation of Specimens and Plating Baths

[0131] (1) Specimen: A cold-rolled steel sheet (SPCC) with a thickness of 0.8 mm and 60 mm x 100 mm was used, and the pretreatment was performed as follows: alkaline degreasing (60°C, 5 min) → washing → 5% hydrochloric acid pickling (room temperature, 3 min) → washing → 2% sodium cyanide activation (room temperature, 30 sec) → washing.

[0132] (2) Basic plating bath: A zinc cyanide plating bath (25 ℃) containing 75 g / L NaOH, 65 g / L NaCN, 26 g / L Zn (M ratio = 2.5), and 5 mL / L commercially available brightener was used.

[0133] (3) Additives: For saccharin, commercially available aqueous saccharin solution (concentration equivalent to 200 g / L) was used, and for butanediol, 2-butyne-1,4-diol aqueous solution (concentration equivalent to 50 g / L) was used.

[0135] 4.2 Plating bath composition of examples and comparative examples

[0136] division Saccharin added (mL / L) Butanediol added (mL / L) Other conditions note Comparative Example 1 0 0 Basic swear words alone Existing method Comparative Example 2 0.5 0 Saccharin alone Plan A Comparative Example 3 0 1.0 Butanediol alone Plan C Comparative Example 4 0.1 0.3 Below the lower concentration limit Outside the range Comparative Example 5 1.5 2.5 Exceeding concentration limit Outside the range Example 1 0.2 0.5 Mixed addition (lower limit) The present invention Example 2 0.5 1.0 Mixed Addition (Intermediate) The present invention Example 3 1.0 2.0 Mixed Addition (Upper Limit) The present invention Example 4 0.3 1.5 Mixed addition The present invention Example 5 0.8 0.8 Mixed addition The present invention

[0138] 4.3 Plating Conditions

[0139] For each plating bath, current was applied under the same conditions of a current density of 4 A / dm², a bath temperature of 25°C, and a plating time of approximately 8 minutes to form a zinc plating layer of approximately 5 μm thickness on the surface of the specimen. After plating, post-treatment was performed as follows: 1st rinsing → 0.5% nitric acid activation (10 seconds) → colored chromate treatment (15 seconds) → 2nd rinsing → 80°C hot air drying.

[0141] 4.4 Evaluation Criteria and Methods

[0142] (1) Presence or absence of whiskers: After the post-treatment specimen was placed in a constant temperature and humidity bath (relative humidity 85%) at 80°C for 5 days, the surface was observed using an optical microscope (magnification 200) and a scanning electron microscope (SEM, magnification 2,000) to evaluate the presence or absence and frequency of whiskers. The evaluation results were classified into four stages: (-): no whiskers, (+): scattered fine whiskers, (++): numerous whiskers, and (+++): severe whiskers.

[0143] (2) Gloss: The gloss (Gloss Unit, GU) was measured using a 60° gloss meter in accordance with KS A 0066. The target specification is 75 GU or higher.

[0144] (3) Current efficiency: The plating thickness in the low current section (0.5 A / dm²) and high current section (7 A / dm²) was measured through a Hull Cell test, and the current efficiency was calculated by comparing it with the theoretical value. The target specification is an average of 75% or more.

[0145] (4) Salt spray test: According to KS D 9502, the time to white rust and red rust was measured while spraying a 5% NaCl aqueous solution at 35°C. The target specifications are 96 hours without white rust and 240 hours without red rust.

[0146] (5) Adhesion: After performing a 180° bend test on the specimen according to KS B 0804, an adhesive tape (width 25 mm) was attached to the bent portion and peeled off to evaluate whether the plating layer peeled off. The target specification is that there is no peeling of the plating layer.

[0148] 4.5 Evaluation Results

[0149] division Whisker Gloss (GU) Current efficiency (average, %) Salt spray test (occurrence of reddish-blue) Adhesion (bending + tape) Comparative Example 1 +++ 62 70 120 hours No peeling Comparative Example 2 + 78 76 240 hours without occurrence No peeling Comparative Example 3 ++ 73 73 192 hours No peeling Comparative Example 4 ++ 68 72 168 hours No peeling Comparative Example 5 + 82 65 240 hours without occurrence Localized exfoliation Example 1 - 77 76 240 hours without occurrence No peeling Example 2 - 85 82 240 hours without occurrence No peeling Example 3 - 88 78 240 hours without occurrence No peeling Example 4 - 82 80 240 hours without occurrence No peeling Example 5 - 80 79 240 hours without occurrence No peeling

[0151] 4.6 Discussion of Evaluation Results

[0152] As confirmed by the results in Table 2, in Comparative Example 1 using only the basic bath, whiskers were severely generated under 5 days of constant temperature and humidity at 80°C (+++), and in the salt spray test, red rust occurred after only 120 hours, significantly reducing reliability.

[0153] In Comparative Example 2, where only saccharin was added, whisker formation was somewhat mitigated (+) but still remained, and in Comparative Example 3, where only butanediol was added, whiskers also formed (++). This suggests that although saccharin has a grain refinement effect, it cannot completely relieve the compressive stress remaining at the grain boundaries, and butanediol also cannot fundamentally prevent whisker nucleation because grain refinement itself does not occur due to its smoothing effect alone.

[0154] In contrast, in Examples 1 to 5, in which 0.2 to 1.0 mL / L of saccharin and 0.5 to 2.0 mL / L of butanediol were added simultaneously, no whiskers were observed in any of them even after 5 days of constant temperature and humidity at 80°C. At the same time, the glossiness was 77 to 88 GU, which stably exceeded the target specification of 75 GU, and the current efficiency was an average of 76 to 82%, which stably exceeded the target specification of 75%. In addition, no red rust occurred during the salt spray test for 240 hours, and no peeling was observed during the adhesion test.

[0155] Meanwhile, in Comparative Example 4, where the additive concentration was below the lower limit of the present invention, the whisker suppression effect was insufficient, and in Comparative Example 5, where the additive concentration exceeded the upper limit of the present invention, the current efficiency was reduced to 65% and localized delamination of the plating layer was observed in the adhesion test, confirming that the additive concentration range of the present invention has critical significance.

[0156] From the above results, it is confirmed that the zinc cyanide plating bath with the addition of a saccharin-butanediol mixture according to the present invention exhibits excellent effects, effectively suppressing whisker generation which was a disadvantage of conventional zinc cyanide plating baths, while improving gloss, current efficiency, corrosion resistance, and adhesion.

[0158] 4.7 Additional Experimental Example - Effects of Plating Thickness and Current Density

[0159] In order to determine how the effect of the present invention is affected by plating thickness and current density, additional tests were performed by changing the plating thickness and current density under the plating bath conditions of Example 2 (saccharin 0.5 mL / L, butanediol 1.0 mL / L).

[0160] As a result of testing with plating thicknesses of 3 µm, 5 µm, 8 µm, 12 µm, and 15 µm, no whiskers were observed under any thickness conditions; however, at a plating thickness of 3 µm, white rust occurred at 96 hours in the salt spray test (no red rust occurred because the absolute thickness of the zinc plating layer was thin), and at a thickness of 5 µm or more, all specifications of no red rust occurring for 240 hours were satisfied.

[0161] In addition, when the current density was changed to 2, 3, 4, 5, 6, 7, and 8 A / dm², no whiskers were observed under any current density conditions; however, at a current density of 8 A / dm², a slightly rough appearance was observed in the high-current portion of the Hull cell test plate, and the glossiness was slightly reduced to about 70 GU. Therefore, for the plating conditions of the present invention, a current density range of 2 to 7 A / dm², particularly 3 to 5 A / dm², is recommended as a stable operating condition.

[0163] 4.8 Additional Experimental Example - Optimization of Additive Concentration Ratio

[0164] In order to more specifically confirm the effect of the concentration ratio of saccharin and butanediol on the whisker inhibition effect in the present invention, additional tests were performed by changing the volume ratio of saccharin to butanediol (based on mL / L) to 1:1, 1:2, 1:3, 1:4, 2:1, and 3:1. Under each condition, the absolute concentration of saccharin was fixed at 0.5 mL / L or an integer multiple thereof (e.g., 1.0 mL / L).

[0165] As a result of the test, whiskers were most effectively suppressed in a volume ratio of saccharin to butanediol in the range of 1:1 to 1:3, and among them, the most excellent whisker suppression and glossiness were simultaneously achieved around 1:2. When the ratio of butanediol exceeded 1:4, a tendency was observed for the plating of the low-current section to become incomplete due to a decrease in plating efficiency, and when the ratio of butanediol was less than 2:1 (i.e., excess saccharin), a tendency was observed for the ductility of the plating layer to decrease somewhat. Therefore, in the present invention, it can be said that setting the volume ratio of saccharin to butanediol to 1:1 to 1:3, more preferably around 1:2, is the most effective.

[0167] 4.9 Additional Experimental Example - Effect of Base Material Type

[0168] In order to confirm whether the effects of the present invention are applicable to various iron-based substrates, plating tests were performed on five substrates: (a) cold-rolled steel (SPCC), (b) hot-rolled steel (SPHC), (c) carburized quenched alloy steel (SCM435), (d) powder metallurgy sintered material (Fe-Cu-C system), and (e) casting (GC250) under the plating bath conditions of Example 2.

[0169] As a result of the test, the plating layer exhibited a uniform glossy appearance for all base materials, and no whiskers were observed during the accelerated test at 80°C and humidity for 5 days. However, in the case of the casting (GC250), the glossiness was measured to be somewhat lower (approx. 70 GU) due to the surface roughness of the base material, and in the case of the powder metallurgy sintered material (Fe-Cu-C system), the surface appeared somewhat rough after plating due to fine pores on the surface; nevertheless, the whisker suppression effect was stably exhibited in all cases. Therefore, the plating method of the present invention has excellent versatility, exhibiting an effect that is relatively insensitive to the type of steel material.

[0171] 4.10 Additional Experimental Example - Effect of Storage Environment After Plating

[0172] In order to confirm whether the plating material of the present invention stably suppresses whisker generation in various storage and usage environments, the surface of the plating material of Example 2 was observed after being exposed to four environments for 6 months, 3 months, 100 cycles, and 5 days, respectively: (a) a room temperature environment of 23 ± 2℃ and 50 ± 10% relative humidity, (b) a high temperature and high humidity environment of 40 ± 2℃ and 90 ± 5% relative humidity, (c) a temperature cycle environment of -10 to +60℃ (1 cycle = 8 hours), and (d) an accelerated environment of 80℃ and 85% relative humidity.

[0173] As a result of the observation, no whiskers were observed in any environment, and it was confirmed that the plating material of the present invention stably suppresses whisker generation not only in actual usage environments but also in accelerated testing environments.

[0175] 4.11 Additional Experimental Example - Quantitative Evaluation Results According to Storage Environment

[0176] The results of the above additional experiment 4.10 are quantitatively summarized as shown in Table 3 below.

[0177] Storage environment Exposure time Whisker formation Maintain surface gloss Whether white-blue or red-blue Room temperature (23℃H 50%) 6 months Non-occurrence 85 → 84GU Non-occurrence High temperature and high humidity (40℃H 90%) 3 months Non-occurrence 85 → 80GU 240 hours without red or blue occurrences Temperature cycle (-10 to +60℃) 100 cycles Non-occurrence 85 → 82GU Non-occurrence Acceleration (80℃-RH 85%) 5 days Non-occurrence 85 → 78GU Surface micro-discoloration Real-world data center environment 6 months Non-occurrence 85 → 84GU Non-occurrence

[0179] 4.12 Additional Experimental Example - Application Evaluation Results by Component

[0180] The evaluation results of applying the bright zinc plating bath of the present invention (composition of Example 2) to various mass-produced parts are summarized in Table 4 below.

[0181] Applicable parts Plating thickness (㎛) Gloss (GU) Whisker (5-day acceleration) Cost compared to conventional methods car wiper linkage 5 ~ 8 82 Non-occurrence equality Medical device frame 8 ~ 12 85 Non-occurrence equality Cage nuts for server racks 5 ~ 7 80 Non-occurrence equality ESS module enclosure 8 ~ 12 78 Non-occurrence equality Distribution panel / distribution panel enclosure 8 ~ 15 76 Non-occurrence equality Circuit breaker enclosure 5 ~ 8 81 Non-occurrence equality Communication equipment enclosure 5 ~ 8 83 Non-occurrence equality

[0183] 4.13 Additional Experimental Example - Plating Bath Monitoring Reference Values

[0184] The monitoring criteria values ​​for stably operating the zinc cyanide plating bath of the present invention on a mass production line are summarized in Table 5 below. The criteria values ​​below are recommended values ​​derived from the results of mass production application of the plating bath of the present invention for more than 6 months.

[0185] Management Items lower limit of management Management limit Analysis cycle Analysis method Sodium hydroxide 70 g / L 80 g / L 2~3 times a week HCl titration Sodium cyanide 50 g / L 75 g / L Once a day AgNO₃ titration zinc 20 g / L 30 g / L Once a day EDTA titration M-B (NaCN / Zn) 2.0 3.0 Once a day calculate lead carbonate - 60 g / L or less Once a month Acid-alkali titration saccharin 0.2 mL / L 1.0 mL / L Once a week Hull Cell exterior · HPLC Butanediol 0.5 mL / L 2.0 mL / L Once a week Hull Cell exterior · HPLC iron impurities - 50 mg / L or less Once a month Atomic absorption Bath temperature 20℃ 30℃ sequence thermometer pH 12 14 Once a day pH meter

[0187] 4.14 Additional Experimental Example - Verification of Working Range by Hull Cell Test

[0188] To confirm whether the additive concentration range of the present invention ensures operational stability, a Hull cell test (Hull cell tank volume 267 mL, current 1 A, plating time 10 minutes) was performed using the plating bath of Example 2. The Hull cell test plate is a test specimen in which the current density changes in one direction, and it is a test method that can simultaneously evaluate the plating appearance over a wide current density range of about 0.1 to 10 A / dm² on the same test plate.

[0189] As a result of the test, a uniform glossy appearance was obtained in the plating bath of the present invention across the entire range of approximately 0.5 to 7 A / dm² of the Hull cell test plate, and a slightly rough appearance was observed only in the high current section exceeding 7 A / dm². This suggests that the plating bath of the present invention has a wide working current density range (working window) compared to conventional baths, thereby ensuring stable plating quality even when plating parts with complex shapes.

[0190] Table 6 below summarizes the working current density range (width of the uniform gloss portion) of the Hull cell test plate and the results of the gloss appearance evaluation of the Hull cell test plate according to the change in additive concentration of the present invention.

[0191] division Saccharin (mL / L) Butanediol (mL / L) Uniform gloss area range (A / dm²) High-current section exterior Low current section exterior H-1 0 0 1.0 ~ 3.0 roughness, blackness False plating H-2 0.5 0 0.8 ~ 4.0 Slightly rough Slightly fake plating H-3 0 1.0 0.7 ~ 5.0 roughness, blackness Good H-4 0.2 0.5 0.5 ~ 6.0 Good Good H-5 0.5 1.0 0.5 ~ 7.0 Excellent gloss Excellent gloss H-6 1.0 2.0 0.5 ~ 7.5 Excellent gloss Excellent gloss H-7 1.5 3.0 0.7 ~ 6.5 Slightly matte Excellent gloss

[0192] As shown in Table 6, in the concentration range of saccharin 0.2 to 1.0 mL / L and butanediol 0.5 to 2.0 mL / L of the present invention, the uniform gloss area of ​​the Hull cell test plate is widely secured to be 0.5 to 6.0 A / dm² or higher. In particular, under conditions H-5 and H-6, a very wide working current density range of 0.5 to 7.0 A / dm² or higher was obtained, confirming that uniform gloss plating can be obtained even on parts with complex shapes without missing plating in low-current areas or rough appearance in high-current areas. On the other hand, when the additive concentration exceeds the upper limit of the present invention, as in comparative condition H-7, a tendency was observed in which excess additives are adsorbed onto the plating layer, causing the gloss to actually decrease.

[0194] 4.15 Additional Experimental Example - Microstructure and Surface Analysis of Plating Layer

[0195] In order to identify the microscopic cause of the whisker suppression effect according to the present invention, for the plating layers of Comparative Example 1 (no additive added) and Example 2 (saccharin 0.5 mL / L + butanediol 1.0 mL / L), (i) measurement of grain size by surface observation using a scanning electron microscope (SEM, magnification 5,000), (ii) measurement of crystal orientation by X-ray diffraction (XRD) analysis and residual stress by the sin²Ψ method, and (iii) measurement of the amount of additive-derived components in the plating layer by X-ray photoelectron spectroscopy (XPS) analysis were performed.

[0196] Table 7 below summarizes the SEM, XRD, and XPS analysis results for the plating layers of Comparative Example 1 and Example 2.

[0197] Analysis Items Comparative Example 1 (no additives added) Example 2 (The present invention) SEM average grain size (㎛) Approximately 3.5 to 5.0 Approximately 0.8 to 1.5 SEM surface morphology Jo Dae-han Ju Sang-jeong, bed protrusion Dense isometric, smooth XRD major orientation plane (002) Strong orientation (101) / (102) uniform orientation XRD average crystallite size (nm) About 80 to 100 About 25 to 35 Residual stress (sin²Ψ, MPa) +85 ~ +120 (Seal) -20 ~ -40 (Compression, Weak) XPS C 1s intensity (relative) 1.0 (standard) Approximately 2.8 (derived from saccharin and butanediol) XPS S 2p detection Undetected Approximately 0.3 at% (saccharin sulfur component) XPS O 1s detection Approximately 1.5 at% Approximately 3.2 at% (hydroxyl groups, etc.)

[0198] From the results of Table 7, it can be seen that the grain size of the plating layer of the present invention was refined to about 1 / 4 to 1 / 5 of the level of the plating layer of Comparative Example 1, and the crystal orientation also changed from a (002) single preferential orientation to a (101) / (102) uniform orientation. In addition, the residual stress changed from a tensile stress of +85 to +120 MPa in Comparative Example 1 to a weak compressive stress of -20 to -40 MPa in Example 2, which means that the stress driving force inside the plating layer was substantially lost. XPS analysis results suggest that the sulfur component of saccharin and the hydroxyl component of butanediol are co-precipitated in small amounts within the plating layer and dispersed at the grain boundaries, thereby contributing to grain refinement and stress relaxation.

[0200] 4.16 Additional Experimental Example - Quantitative Comparison with Prior Art

[0201] In order to quantitatively compare the effects of the present invention with conventional whisker suppression methods, five plating materials were evaluated under the same accelerated test conditions (80°C, relative humidity 85%, 5 days): (a) Comparative Example 1 (zinc cyanide plating without additives), (b) zinc-nickel alloy plating (Ni 12%, commercially available acid bath), (c) heat treatment at 200°C for 1 hour after zinc cyanide plating, (d) copper strike plating (2 μm) before zinc cyanide plating, and (e) Example 2 (the present invention).

[0202] Table 8 below is the result of a quantitative comparison between the conventional whisker suppression method and the bright zinc plating method of the present invention in terms of whisker suppression effect, plating quality, process cost, and energy consumption.

[0203] Evaluation items (a) Comparative Example 1 (b) Zn-Ni plating (c) Heat treatment (D) Cu strike (e) Example 2 Whisker occurrence frequency +++ (Severe) - (Non-occurrence) + (scattered) + (scattered) - (Non-occurrence) Gloss (GU) About 45 About 60 About 70 About 70 About 85 Current efficiency (%) About 78 About 60 to 70 About 78 About 75 About 80 Salt spray 240Hr Red-Blue generation Non-occurrence generation Non-occurrence Non-occurrence Number of process steps standard +2 (Acidity Conversion) +1 (heat treatment) +1 (Cu Strike) Same (add only) Energy consumption (relative) 1.0 About 1.2 About 1.8 About 1.3 About 1.0 Equipment investment standard New bathtub and rectifier heat treatment furnace New bathtub Unnecessary Carbon emissions (relative) 1.0 About 1.2 About 1.7 About 1.3 About 1.0

[0204] As shown in Table 8, Example 2 of the present invention completely suppresses whisker generation to a level equivalent to that of the conventional method (b), zinc-nickel alloy plating, while demonstrating results that surpass all conventional methods in terms of gloss, current efficiency, and corrosion resistance. In particular, unlike the conventional methods (b) to (d), the present invention achieves an equivalent or superior whisker suppression effect by adding only trace amounts of saccharin and butanediol to the existing zinc cyanide plating bath without the need for additional processes or equipment investment; thus, a reduction effect of approximately 17 to 41% in energy consumption and carbon emissions compared to the conventional method can be expected. These quantitative comparison results clearly support the industrial utility of the present invention.

[0206] 5. Example of actual mass production inline application

[0207] The inventors adopted the composition of Example 2 (saccharin 0.5 mL / L, butanediol 1.0 mL / L) and performed inline plating on various mass-produced parts, such as automobile wiper linkages, medical device frames, cage nuts for data center server racks, and electrical circuit switching device parts.

[0208] Mass production inline plating was performed in the following order: (i) alkaline degreasing (NaOH 30 g / L, sodium carbonate 20 g / L, 60℃, 5 ~ 10 min, cathode electrolysis 1 ~ 3 A / dm²), (ii) first rinse, (iii) pickling (10 % HCl, room temperature, 3 ~ 5 min), (iv) second rinse, (v) activation (NaCN 2 ~ 3 g / L, room temperature, 30 ~ 60 sec), (vi) zinc cyanide plating (bath of the present invention, 25℃, 4 A / dm², 5 ~ 8 μm), (vii) third rinse, (viii) nitric acid activation (0.5 % HNO₃, 10 sec), (ix) colored chromate treatment (15 ~ 30 sec), (x) fourth rinse, and (xi) 80℃ hot air drying.

[0209] As a result of mass production inline plating, the plating appearance, gloss, current efficiency, and corrosion resistance were all reproduced at a level substantially equivalent to the laboratory results, and no whiskers were observed even after the mass-produced specimens were exposed to a data center environment (23 ± 2℃, relative humidity 50 ± 10%) for 6 months. In addition, no whiskers were observed in the whisker accelerated test (80℃, relative humidity 85%), confirming that the effects of the present invention are stably reproduced even on a mass production scale.

[0210] In particular, when applied in-line during mass production, since the concentration of additives in the plating bath decreases slightly as the operation progresses, it is desirable to perform periodic monitoring through the analysis of the appearance and plating thickness of the Hull cell test plate, and to replenish saccharin in units of 0.05 to 0.1 mL / L and butanediol in units of 0.1 to 0.2 mL / L every 7 to 10 days. By replenishing in advance before the additive concentration reaches the lower limit concentration of the present invention, the continuity of the whisker suppression effect can be ensured.

[0211] In addition, if the decomposition products (carbonates, sodium carbonate) accumulated in the plating bath exceed a certain concentration (e.g., 60 g / L), bath management is required through partial bleeding of the bath and replenishment of fresh water, and in this case, the concentration of additives must be readjusted to within the range of the present invention.

[0213] 5.1 Application Examples for Automotive Wiper Linkages

[0214] An automotive wiper linkage is a component that converts the rotational motion of a wiper motor into the reciprocating motion of a wiper blade, and is a key safety component for ensuring visibility of a vehicle. When the zinc cyanide plating bath of the present invention was applied to the plating of an automotive wiper linkage (weight approximately 150 g, surface area approximately 80 cm² / piece), excellent results were obtained despite the complex shape of the part, including (i) the plating thickness of the inner shape portion being uniformly distributed at 70% or more of the outer shape portion, (ii) an average gloss of 80 GU or more, (iii) no whiskers occurring after 5 days of constant temperature and humidity at 80°C, and (iv) no red rust occurring in a 240-hour salt spray test.

[0216] 5.2 Application Examples for Medical Device Frames

[0217] Frame components of medical devices, particularly ultrasound imaging diagnostic devices or patient monitoring equipment, are trending toward wider and thinner shapes, which leads to complex stress distribution in thin-plate structures. When the zinc cyanide plating bath of the present invention was applied to the plating of a medical device frame (SPCC, thickness 1.6 mm), (i) a uniform glossy appearance was obtained even in the thin-plate processing section, (ii) no whiskers were generated in the accelerated test, and (iii) excellent adhesion was exhibited without peeling or bubbling of the coating film in the subsequent powder coating process.

[0219] 5.3 Application Examples for Data Center Server Rack Components

[0220] Cage nuts, risers, and hanger accessories for data center server racks are part groups of components where reliability degradation due to whiskers is of the greatest concern, as they are operated for a long period in a constant temperature and humidity environment of a data center after plating. As a result of applying the plating bath of the present invention to these components, no whiskers were found not only in an accelerated test of 5 days in a constant temperature and humidity environment of 80°C, but also in surface observation after 6 months of exposure in an actual data center environment of 23 ± 2°C and relative humidity of 50 ± 10%.

[0222] 5.4 Application Examples for ESS, Switchboard, and Distribution Panel Enclosure Components

[0223] Since module enclosures of ESS (Energy Storage Systems), as well as enclosures and components of switchboards and distribution boards, are installed near circuits to which high DC voltage or high AC current is applied, short-circuit accidents caused by whiskers can lead directly to serious accidents such as fire or explosion. As a result of applying the plating bath of the present invention to these components, no whiskers were detected in both accelerated tests and long-term exposure tests, confirming that it can directly contribute to improving the safety of electrical and electronic components.

[0225] 5.5 Application Examples for Electrical Circuit Switching and Protection Device Components

[0226] The enclosures and internal support components of electrical circuit switching and protection devices, such as circuit breakers and disconnectors, are subjected to vibration stress due to switching operations after plating, and there is a risk that this vibration stress may combine with residual stress in the plating layer to accelerate whisker formation. As a result of applying the plating bath of the present invention to electrical circuit switching device components of Sanjeon Precision Co., Ltd., Sungshin Electric Co., Ltd., etc., no whiskers were found in the accelerated whisker test after the vibration acceleration test (20 to 2,000 Hz, 24 hours).

[0228] 6. Application Fields and Examples of Use

[0229] The polished zinc plating method according to the present invention can be applied to all fields where reliability degradation caused by whiskers is a problem. Representative application fields are as follows.

[0230] (1) Structural materials, risers, cage nuts, server rack frames, and access floor supports for data centers and server rooms

[0231] (2) Frames and exterior parts of medical devices (e.g., ultrasound diagnostic devices, medical imaging equipment, etc.)

[0232] (3) Automotive electronic and interior parts such as automotive wiper linkages, seat parts, door module parts, etc.

[0233] (4) Enclosure of ESS (Energy Storage System) module, enclosure of switchboard / distribution board and accessory parts

[0234] (5) Enclosure parts of electrical circuit switching and protection devices (circuit breakers, disconnectors, etc.)

[0235] (6) Enclosures and support parts of 5G communication equipment and cloud infrastructure equipment

[0237] 7. Modified embodiment

[0238] The present invention is not limited by the above embodiments and can be implemented with various modifications within the scope of the technical concept of the present invention. For example, saccharin may be used in combination with some of other sulfonimide compounds known as conventional primary polishing agents, such as para-toluenesulfonamide (p-TSA) and benzosulfonamide, and butanediol may be additionally used in combination with a leveling agent such as polyethylene glycol (PEG). However, to achieve the core effect of the present invention (whisker inhibition), the mixed addition of 0.2 to 1.0 mL / L of saccharin and 0.5 to 2.0 mL / L of butanediol is essential.

[0239] In addition, the zinc cyanide plating bath in the present invention is not limited to a cyanide bath, and in light of its operating principle, the concentration range of the additive of the present invention is expected to be applicable to alkaline non-cyanide zinc plating baths or zinc chloride plating baths as well, but the most stable and reproducible whisker suppression effect was confirmed in a cyanide bath.

[0240] In addition, the plating method of the present invention can be applied to various iron-based substrates such as general steel, alloy steel, casting, forging, and powder metallurgy materials, and any of the following can be applied for surface passivation treatment after plating: colored chromate, colorless chromate, black chromate, blue trivalent chromium passivation, black trivalent chromium passivation, etc.

[0242] 7.1 Method for Preparing New Solution for Zinc Cyanide Plating Bath

[0243] The fresh solution for the zinc cyanide plating bath of the present invention can be prepared as follows, for example: (i) Fill a clean plating bath with pure water (or ion-exchanged water) equivalent to about 50% of the bath's volume. (ii) Slowly add and dissolve sodium hydroxide (NaOH) while stirring. Since the dissolution of sodium hydroxide is an exothermic reaction, care must be taken not to let the liquid temperature exceed 40°C. (iii) After the liquid temperature has cooled to 30°C or lower, add and dissolve sodium cyanide (NaCN). (iv) Slowly add zinc oxide (ZnO) powder or zinc cyanide (Zn(CN)₂) and stir and dissolve sufficiently until the liquid becomes transparent. (v) Add activated carbon (about 3 to 5 g / L) and stir for 30 minutes to adsorb and remove trace organic impurities, then filter with filter paper (nominal 5 μm). (vi) Transfer the filtrate to a clean plating tank and add pure water to adjust the volume to the capacity of the plating tank. (vii) Add the brightener and the additives of the present invention (saccharin, butanediol) according to the concentration range of the present invention, stir sufficiently for 1 hour, and then let it stand for about 24 hours (aging).

[0244] In the above process of preparing the new solution, among the additives of the present invention, saccharin is typically sold in powder form or as a concentrated aqueous solution of about 200 to 300 g / L, and butanediol is sold in liquid stock form or as an aqueous solution of about 50 to 100 g / L. Depending on the commercially available concentrated form, the amount to be applied is determined by converting it to the concentration range of the present invention (saccharin 0.2 to 1.0 mL / L, butanediol 0.5 to 2.0 mL / L).

[0246] 7.2 Comparison with Conventional Whisker Suppression Methods

[0247] In order to compare the whisker suppression effect of the present invention with conventional whisker suppression methods, plating was performed on the same SPCC specimen using four methods: (a) the plating method of the present invention (Example 2), (b) heat treatment at 180°C for 4 hours after conventional zinc cyanide plating, (c) zinc-nickel alloy plating (Ni content about 12%), and (d) zinc cyanide plating after copper strike plating, and an accelerated whisker test (at 80°C constant temperature and humidity for 5 days) was performed.

[0248] As a result of comparison, the plating method of the present invention and the conventional methods (b), (c), and (d) all satisfied the whisker-free specification. However, (b) has the disadvantage that additional energy is required for heat treatment after plating and the gloss level drops to about 65 GU; (c) has the disadvantage that the unit cost of the plating bath is about 2.5 times higher than that of the present invention and additional wastewater treatment costs are incurred; and (d) has the disadvantage that a separate copper strike plating tank must be added in-line. In contrast, the present invention achieves the whisker-free specification equally without additional processes, additional equipment, or additional energy, and is superior to any conventional method in terms of overall cost efficiency.

[0250] 7.3 Environmental Effects

[0251] The plating method of the present invention is estimated to provide a power saving effect of approximately 0.5 to 1.5 kWh per 1 kg of part compared to conventional post-plating heat treatment methods. Assuming a plating line with an average part weight of 0.5 kg and a monthly production capacity of 500,000 units, there is an annual power saving effect of approximately 150 to 450 MWh. When applying the CO₂ emission factor of the average Korean electricity (approx. 0.4 kg-CO₂ / kWh), this translates to an annual reduction in CO₂ emissions of approximately 60 to 180 tons. Therefore, the present invention can be considered an environmentally friendly plating technology that directly contributes to carbon neutrality policies and ESG management principles.

[0253] 7.4 Industrial Significance of the Present Invention

[0254] The present invention has the following industrial significance. First, the present invention allows the use of existing equipment such as plating tanks, rectifiers, and charging jigs in a zinc cyanide plating line, and can be applied immediately by simply adjusting the additives to fit the scope of the present invention. Accordingly, whisker suppression effects can be implemented in mass production sites in a short period of time without the burden of equipment investment.

[0255] Second, compared to conventional zinc-nickel alloy plating, the unit cost of plating bath chemicals in the present invention is about 1 / 2 to 1 / 3, and no additional wastewater treatment costs are incurred to remove nickel components from the wastewater. This leads to a direct reduction in plating unit costs, allowing for a reduction of approximately 30 to 50 percent in plating processing costs.

[0256] Third, since the present invention does not require stress relief heat treatment (180 to 200°C, 1 to 4 hours) after plating, the electricity and city gas energy required for operating the heat treatment furnace are reduced. In addition, since there is no concern about discoloration of the plating layer or deterioration of appearance due to heat treatment, it can be directly applied to decorative parts and exposed parts where a glossy appearance is important.

[0257] Fourth, the present invention effectively relaxes residual stress in the plating layer with only trace amounts of saccharin and butanediol, thereby achieving a reduction in residual stress of about 50% or more compared to conventional plating materials at the same plating thickness. This improves the long-term reliability of the plating material and prevents whiskers from forming even after accelerated testing and exposure to actual environments for more than 6 months.

[0258] Fifth, the present invention can be applied to various application fields such as data centers, server racks, medical devices, automotive electronic components, ESS enclosures, switchboards, and communication equipment using the same plating bath composition and plating conditions, thus having the advantage of line operation that there is no need to separate plating lines by component group.

[0260] 7.5 Summary of the Excellence of the Present Invention

[0261] The gloss zinc plating method of the present invention simultaneously satisfies five performance indicators: (i) no whisker generation, (ii) glossiness of 80 GU or higher, (iii) plating current efficiency of 78% or higher, (iv) no red rust generation in a salt spray test for 240 hours, and (v) no peeling in the bending and peeling adhesion test according to KS B 0804. This means that the present invention simultaneously achieves multiple performance indicators that are difficult to achieve simultaneously with any single whisker suppression method.

[0262] In particular, the plating material of the present invention exhibits extensive environmental resistance, such that whiskers do not form even after 5 days of exposure in an accelerated environment at 80°C and 85% relative humidity, whiskers do not form even after 100 temperature cycles from -10 to +60°C, and whiskers do not form even after 6 months of exposure in a general environment at 23°C and 50% relative humidity. This excellent environmental resistance demonstrates that the plating material of the present invention can maintain reliability in various real-world environments, such as the constant temperature and humidity environment of a data center, the engine room environment of an automobile, and the heat-generating environment inside a server rack.

[0263] The inventors would like to add that the plating bath composition and plating conditions according to the present invention are not obvious matters that can be easily modified or implemented by a person skilled in the art. That is, the core of the present invention lies not merely in adding saccharin or butanediol individually, but in adding a mixture of these two additives within the concentration range defined in the present invention (saccharin 0.2 to 1.0 mL / L and butanediol 0.5 to 2.0 mL / L). According to the inventors' experiments, adding only one of the two additives alone results in whiskers occurring sporadically (Comparative Examples 6, 7) or in large numbers (Comparative Examples 8, 9), and furthermore, when the concentration of the two additives falls outside the range of the present invention (Comparative Example 10), the whisker suppression effect is not sufficiently achieved. This implies that the mixed concentration range of the two additives defined in the present invention is a critical range that simultaneously optimizes the three actions of grain refinement, residual stress relaxation, and surface smoothing.

[0264] Although the present invention has been described above by means of preferred embodiments, the scope of the present invention is defined by the claims set forth below, and it will be obvious to those skilled in the art that various modifications and equivalent modifications are possible within the scope of the technical concept of the present invention.

Claims

Claim 1 A bright zinc plating method comprising the step of immersing a workpiece in a zinc cyanide plating bath and applying current to form a zinc plating layer on the surface of the workpiece, wherein the zinc cyanide plating bath is composed by adding 0.2 to 1.0 mL / L of saccharin and 0.5 to 2.0 mL / L of butanediol to a base bath comprising 70 to 80 g / L of sodium hydroxide, 50 to 75 g / L of sodium cyanide, 20 to 30 g / L of zinc, and a brightener, wherein the butanediol comprises 2-butyne-1,4-diol, and the volume ratio of the saccharin to the butanediol (saccharin:butanediol) is 1:1 to 1:3, and the bright zinc plating method comprises a separate heat treatment step for stress relief after the zinc plating layer formation step. A bright zinc plating method characterized by not involving, and the formed zinc plating layer having a residual compressive stress of 60 MPa or less as measured by X-ray diffraction (XRD) sin²Ψ method, and not showing whiskers when observed at 200x magnification under an optical microscope after being left for 5 days under constant temperature and humidity conditions of 80℃ and 85% relative humidity. Claim 2 A bright zinc plating method according to claim 1, characterized in that the ratio of the concentration of sodium cyanide to the concentration of zinc (NaCN / Zn, M ratio) in the zinc cyanide plating bath is 2.0 to 3.

0. Claim 3 delete Claim 4 A bright zinc plating method according to claim 1, wherein the zinc plating layer forming step is performed under conditions of a bath temperature of 20 to 30℃ and a current density of 2 to 8 A / dm², and the thickness of the zinc plating layer formed is 3 to 15 μm. Claim 5 A bright zinc plating method according to claim 1, characterized by further including a washing step, a nitric acid activation step, a colored chromate or trivalent chromium passivation step, and a drying step after the zinc plating layer formation step. Claim 6 delete Claim 7 A polished galvanizing method according to claim 1, characterized in that the polished galvanizing method is applied to any one selected from the group consisting of structural materials for data centers, server racks, medical device frames, automobile wiper linkages, housing parts for ESS modules, and enclosure parts for electrical circuit switching and protection devices. Claim 8 A polished zinc plating method according to claim 1, characterized in that the polished zinc plating method has a working range in which a uniform polished appearance is obtained over a current density range of 0.5 to 7.0 A / dm² in a Hull Cell test. Claim 9 A galvanized material comprising a galvanized layer formed by a polished galvanizing method according to claim 1, wherein the galvanized layer has a residual compressive stress of 60 MPa or less as measured by the X-ray diffraction (XRD) sin²Ψ method, and no whiskers are generated when observed at an optical microscope magnification of 200x after being left for 5 days under constant temperature and humidity conditions of 80℃ and 85% relative humidity. Claim 10 A zinc-plated material according to claim 9, wherein the zinc-plated layer is characterized in that crystal plane diffraction peaks (002), (101), and (102) are all detected in X-ray diffraction (XRD) analysis, and the ratio of the intensity of each diffraction peak is in the range of (002):(101):(102) = 1:0.5 or higher : 0.3 or higher, and a strong single-plane preferential orientation is not formed. Claim 11 In claim 9, the zinc-plated material is characterized by not developing red rust for 240 hours in a salt spray test according to KS D 9502, having a gloss level of 75 GU or higher according to a 60° gloss meter, and not developing peeling of the plating layer in a bending test according to KS B 0804. Claim 12 delete Claim 13 A zinc cyanide plating bath composition for whisker inhibition, comprising 70 to 80 g / L sodium hydroxide, 50 to 75 g / L sodium cyanide, 20 to 30 g / L zinc, a brightener, 0.2 to 1.0 mL / L saccharin, and 0.5 to 2.0 mL butanediol, wherein the butanediol comprises 2-butyne-1,4-diol, and the volume ratio of the saccharin to the butanediol (saccharin:butanediol) is 1:1 to 1:

3. Claim 14 A zinc cyanide plating bath composition for whisker inhibition according to claim 13, characterized in that the ratio of the concentration of sodium cyanide to the concentration of zinc (NaCN / Zn) is 2.0 to 3.

0. Claim 15 delete Claim 16 delete Claim 17 delete Claim 18 delete

Citation Information

Patent Citations

  • High-corrosion-resistant environment-friendly galvanization technological method

    CN105420766A

  • SOLUTION CONCENTRATION AUTOMATIC DEVICE AND METHOD

    JP1993274044A

  • Method for manufacturing electro galvanized steelsheets having high gloss

    KR1020020053290A

  • Zinc plated steel having iron flash plating film thereon and composition of bath of iron flash plating and method for manufacturing the zinc plated steel

    KR1020090112919A

  • Excellent activation whisker resistant zinc coating method for electrical and electronic components

    KR1020200079049A